The effect of giving gibberellin at different concentrations on the elongation of palm oil palm oil (borrassus flabelifer) - Luat, Andreas; Yusnaeni, Yusnaeni; Ardan , Andam S. (Universitas Wiralodra, 2023)
This research has been carried out in the greenhouse of BAPEDALDA NTT. The method used was an experimental method with a completely randomized design consisting of 4 (four) treatments, namely control (G0), giving gibberellin 100 ppm (G1), gibberellin 200 ppm (G2), and gibberellin 300 ppm (G3), each treatment consisted of 4 (four) replications so that the total experimental unit was 16 units. The parameters of this study were apokol elongation and the percentage of palmyra growth. The data obtained were analyzed using analysis of variance (ANOVA), and continued with the honest significant difference test (BNJ) if there is a difference. The results showed a significant difference between the control and the gibberellin treatment for the apokol length parameter. Meanwhile, the percentage of palm growth showed no effect. The results of the analysis of variance for the average parameter of apokol elongation obtained F-Count > F-Table, where F-Count = 6.67 and F-Table 5% = 3.49. This means that there is an effect of giving gibberellins on the length of the apokol ejection. Because there are differences, it is continued with the Honest Significant Difference (BNJ) test. The results of the BNJ test showed that the G2 treatment was not different from the G1 and G0 treatments and was different from the G3 treatment. The G1 treatment was not different from the G0 treatment but different from the G3 treatment. The G0 treatment was no different from the G3 treatment.